Basic Fibroblast Growth Factor Suppresses Retinal Neuronal Apoptosis in Form-Deprivation Myopia in Chicks - Mao, Junfeng; Liu, ShuangzhenLiu; Wen, Dan; Tan, Xingping; Fu, Chunyan (Current eye research, 2006)
Purpose: Chorioretinal atrophy including retinal neuronal apoptosis occurred in chronic form-deprivation myopia induced by lid suture in chicks. We investigated whether exogenous basic fibroblast growth factor (bFGF) could simultaneously inhibit the excessive axial elongation and retinal neuronal loss in the myopic chick eyes. Methods: Unilateral form deprivation was produced in neonatal male Hyline chicks by lid suture 24 hr after hatching. Ten microliters of solution containing 5 ng bFGF or PBS (vehicle) was injected into the vitreal chamber at 10 weeks of age, once every 3 days until week 12, when the animals were sacrificed. Ocular refraction and axial length were assessed by retinoscopy and calipers at the age of 12 weeks. Retinal apoptotic neurons and their caspase-3-like protease activity were analyzed by transmission electron microscopy, the terminal-deoxynucleotidyl transferase-mediated biotin-deoxyuridine triphosphate nick-end labeling (TUNEL) staining, and a colorimetric method using Ac-DEVD-pNA as a substrate. The number of TUNEL-positive cells was counted to analyize the survival activity of bFGF on retina. Results: After 12 weeks of lid suture, the control eyes were either emmetropic or hyperopic, whereas the deprived eyes became myopic with axial length increased. TUNEL-positive nuclei, condensed nuclear chromatin, and apoptotic bodies were observed in posterior retinal outer nuclear layer (ONL) and inner nuclear layer (INL) in the myopic chick eyes. Activity of retinal caspase-3-like protease in these eyes was elevated. In addition to ameliorating myopic ocular growth, intravitreal bFGF therapy significantly reduced the number of retinal apoptotic neurons and downregulated caspase-3 activity. Conclusions: Exogenous bFGF effectively ameliorates the excessive axial elongation and retinal neuron apoptosis in chronic form-deprivation myopia in chicks. It is possible that bFGF will be a promising therapeutic agent for high human myopia.